ANALISIS ATAS KEBIJAKAN TAX AMNESTY DI INDONESIA DAN IMPLIKASINYA TERHADAP PENINGKATAN PENDAPATAN PAJAK - Sipayung, Baren (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The history of Tax Amnesty which was first implemented in 1964 then continued in 2016 with the enactment of Law of the Republic of Indonesia Number 11 of 2016 concerning Tax Amnesty. Furthermore, tax amnesty or tax amnesty (English: Tax Amnesty) is also a time-limited opportunity for certain groups of taxpayers to pay a certain amount of tax as an amnesty for the obligation to pay taxes (including the waiver of interest and penalties) related to the tax period. previously without fear of criminal prosecution. Tax Amnesty is a public policy that is formally stipulated based on Law 11/2016 as a tool to collect state revenues from the tax sector (tax revenue) quickly in a relatively short period of time against the backdrop of widespread tax avoidance. Meanwhile, the expected benefit of the Tax Amnesty policy is to increase the inflow of funds from abroad which in the long term can be used as a driving force for investment which in turn is beneficial to stimulate the national economy. This article describes the weaknesses of the tax amnesty policy, including recommendations to overcome these weaknesses.